Electrode Build‐Up of Reducible Metal Composites toward Achievable Electrochemical Conversion of Carbon Dioxide. Issue 4 (26th November 2015) - Lee, Seunghwa; Lee, Jaeyoung
Abstract: At the beginning of the 21st century, our world is faced with a global‐warming problem due to the continuous increase in carbon dioxide emission, and thus, the development of novel experimental techniques is needed. The electrochemical conversion of carbon dioxide into high‐value organic compounds could be of vital importance to solve this issue. The biggest challenge has always been to develop an electrocatalyst that is chemically active and structurally stable. Herein, previous studies, recent approaches, and current points of view on the electrode structure of metal oxide composites for the advanced electrochemical conversion of carbon dioxide are reviewed. Abstract : Finding the active species : Electrochemical conversion of CO2 into high‐value compounds by using oxidized metal electrode structures offers superior catalytic activity, selectivity, and stability. Previous studies and current, differing points of view on the utilization of reducible metal composites are discussed. The approaches could hopefully help in the development of catalysts rationally designed for the CO2 electrolysis and ultimately complete carbon‐recycling systems.